Volatile Organic Compounds of Streptomyces sp. TOR3209 Stimulated Tobacco Growth by Up-Regulating the Expression of Genes Related to Plant Growth and Development - He, Yuxi; Guo, Wenyu; Peng, Jieli; Guo, Jinying; Ma, Jia; Wang, Xu; Zhang, Cuimian; Jia, Nan; Wang, Entao; Hu, Dong; Wang, Zhanwu (Frontiers in Microbiology, 2022)
The PGPR strain Streptomyces sp. TOR3209 isolated from rhizosphere of tomato could increase disease resistance, promote growth of several plants, and modify the rhizosphere microbial community. However, the mechanism of these effects maintains unclear and the growth promotion by directly inoculating this strain to plant roots was not significant in some cases. Considering the regulatory role of microbial volatile organic compounds (VOCs) in plant growth and development, we hypothesize that the strain TOR3209 might benefit the plants by producing VOCs. To verify this hypothesis, VOCs produced by TOR3209 were collected and used to treat the tobacco and tomato seedlings. The results proofed that the TOR3209 VOCs increased the fresh weight of tobacco in I-plate up to 119% than that of CK. In pot experiment with miniature greenhouse, the VOCs increased the total dry weight of tomato about 39%, and promoted the root development, compared with that in CK. Remarkably, study on transcriptional changes in plants treated with the VOCs revealed that the highest gene differential expression was observed on UDP-glycosyltransferase, Glutamate receptor, RING/U-box protein with C6HC-type zinc finger and Leucine-rich repeat receptor-like protein kinase family protein, all being involved in plant growth and development processes. By solid phase micro extraction (SPME) method, 2,4-bis(1,1-dimethylethyl)-phenol and hexanedioic acid dibutyl ester were found as the main VOCs produced by TOR3209. In this study, we revealed that the VOCs produced by strain TOR3209 could regulate plant growth in a non-contact manner, and further efforts will be made to explore the effective VOCs in biological promotion.